2018
DOI: 10.1007/s12105-018-0945-z
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Microcystic Adenocarcinoma: Report of a Rare Case and Review of Literature

Abstract: Sclerosing microcystic adenocarcinoma is an exceedingly rare entity occurring in the mucosal surfaces of the head and neck that closely resembles cutaneous microcystic adnexal carcinoma. Here, we report a case of sclerosing microcystic adenocarcinoma that presented as a vague mass at the floor of the mouth in a 55-year-old woman. The pathology features and the diagnostic challenges, especially in the biopsy and margin evaluation are discussed here. Similar cases published in the English literatures are reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…To our knowledge, this is the first study to profile SMA at the molecular level (1,6). Previous studies have attempted molecular characterization of MAC; SMA has often been described as a variant of MAC owing to its histological resemblance to sweat glands and infiltrative pattern and tendency toward perineural invasion but with a more favorable prognosis (1)(2)(3)8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study to profile SMA at the molecular level (1,6). Previous studies have attempted molecular characterization of MAC; SMA has often been described as a variant of MAC owing to its histological resemblance to sweat glands and infiltrative pattern and tendency toward perineural invasion but with a more favorable prognosis (1)(2)(3)8).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have observed SMA in the context of treatment with immunosuppression. One case report involved a patient treated with glatiramer for multiple sclerosis, while another involved a patient undergoing stem cell transplantation for AML (1,6). The patient in this case report previously received treatment with methotrexate, infliximab, adalimumab and apremilast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editors, Our attention has been drawn to the recent report by Zhang et al [1], describing a single additional case of sclerosing microcystic adenocarcinoma, bringing to nine the number of examples documented in the English language literature [2][3][4][5]. Although the term "microcystic adenocarcinoma" was originally attributed to Mills et al [4] in 2016 [1,5], it is pertinent to make a few comments here on the first proposal of this entity in 2008 by Rosebush et al [6] that escaped the attention of the vast majority of pathologists.…”
mentioning
confidence: 99%
“…Following a report by Johnston and Toker [7] in 1982, a number of definite or possible cases of salivary microcystic adenocarcinoma with sclerosing features were documented under a variety of names [1][2][3][4][5][6][8][9][10]. Without much supportive rationale, sclerosing microcystic adenocarcinoma is now only the designation that has survived this terminological conundrum [1,5]. Readers interested in the previously discarded terms are referred to two review articles [5,9].…”
mentioning
confidence: 99%